EFFORTS OF RAISING THE TERRORIST SEPARATISTS WEST PAPUA REVOLUTIONARY ARMY IN BORDER REGION RI - PNG - Araf, Sulthan; Wardoyo, Broto; Nurish, Amanah (Journal of Terrorism Studies, 2021)
TRWP (West Papua Revolutionary Army) is the most important part of the Terrorist Separatist Group (KST) which is an armed group with the main goal of seceding from the Unitary State of the Republic of Indonesia. This group is also a group that exists in the papua province based in the border area of Indonesia, precisely in Kampung Yako State of Papua New Guinea. The history records, this Terrorist Separatist Group stand with the aim of the liberate West Papua, believing it’s not a unity with the State of Indonesia or other Countries. Those who continue to survive and struggle to spread radicalism stand to separate themselves from the Sovereign State of the Republic of Indonesia with the main mission to liberate West Papua from the Government of Indonesia. In 2018 the Government of Indonesia designated TRWP as KST in accordance with Law No. 5 of 2018 on Terrorism. As a form of seriousness tni - AD in KST fundraising efforts, the TNI - AD Intelligence Datasemen unit formed a Vulnerable Area Security Post located in Skouw Papua around the Cross-Border Post area which one of its main programs conducts Investigation, Security and Fundraising of KST Members.